A chemometric approach for determining the reaction quantum yields in consecutive photochemical processes. Issue 32 (2nd August 2017) - Marcolongo, Juan P.; Schmidt, Juan; Levin, Natalia; Slep, Leonardo D.
Abstract : Chemometrics helps in determining the quantum yields of multistep photoreactions and allows the deconvolution of the spectra of the colored intermediates. Abstract : A chemometric procedure to deal with spectroscopically monitored processes involving photochemical steps is fully described. The methodology makes it possible to work with reactions that involve several components with unknown (and eventually overlapping) spectra and provides a tool for the simultaneous determination of both the quantum yields of the reaction and the spectra of all the species present in a multi-step photochemical process. As a benchmark, we apply these ideas to extract the quantum yields of photodetachment of coordinated ligands employing data recorded over the course of the decomposition of [Ru(tpm)(bpy)(CH3 CN)] 2+ and cis -[Ru(bpy)2 (CH3 CN)2 ] 2+ under stationary photolysis conditions. The approach is fast and robust and it is easily implemented in scientific programming languages.